2018
DOI: 10.3847/1538-4365/aab777
|View full text |Cite
|
Sign up to set email alerts
|

Cyberhubs: Virtual Research Environments for Astronomy

Abstract: Collaborations in astronomy and astrophysics are faced with numerous cyber infrastructure challenges, such as large data sets, the need to combine heterogeneous data sets, and the challenge to effectively collaborate on those large, heterogeneous data sets with significant processing requirements and complex science software tools. The cyberhubs system is an easy-to-deploy package for small to medium-sized collaborations based on the Jupyter and Docker technology, that allows web-browser enabled, remote, inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Documentation on how to use the codes is provided in the form of iPython Jupyter notebooks and is cited in the following subsections. Although installing the code is relatively straightforward, the installation can be bypassed by using the online virtual cyberhubs 3 environment (Herwig et al 2018).…”
Section: Chemical Evolution Codesmentioning
confidence: 99%
“…Documentation on how to use the codes is provided in the form of iPython Jupyter notebooks and is cited in the following subsections. Although installing the code is relatively straightforward, the installation can be bypassed by using the online virtual cyberhubs 3 environment (Herwig et al 2018).…”
Section: Chemical Evolution Codesmentioning
confidence: 99%
“…Near [Fe/H] = 0, our predictions (solid line) have a bump that overestimates disk data by almost an order of magnitude. The 20 M stellar model at Z = 0.01 is at the origin of the Cr bump (see also Figure 7 in Herwig et al 2018). When removing this stellar model from the yields set, the bump disappears entirely (dashed line in Figure 1).…”
Section: Galactic Chemical Evolution Modelmentioning
confidence: 93%
“…Here we discuss the impact of silicon-carbon (Si-C) shell mergers on the evolution of chromium (Cr) in the Milky Way. Since the publication of the second set of NuGrid yields (Ritter et al 2018b), an overproduction of Cr at galactic scale has been reported by Herwig et al (2018) and Philcox et al (2018) when using these yields in GCE codes. We have isolated the source of this overproduction.…”
Section: Introductionmentioning
confidence: 99%
“…[45]. The calculations were performed using the post-processing nucleosynthesis code MPPNP [46], which was developed by the NuGrid collaboration. The code takes as an input the stellar evolution trajectories calculated by the one-dimensional stellar evolution code MESA [84].…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…[45]. For the simulations, we used a multi-zone postprocessing code, MPPNP [46], to study the sensitivity at various stellar masses and initial metallicities. The simulations also demonstrate, in a more general way, the sensitivity of the abundance to the ambiguous reaction rates, by varying the α cluster strength of relevant 22 Ne + α resonances.…”
Section: Introductionmentioning
confidence: 99%